2019
DOI: 10.2903/j.efsa.2019.5765
|View full text |Cite
|
Sign up to set email alerts
|

Pest categorisation of Spodoptera litura

Abstract: The EFSA Panel on Plant Health (PLHP) performed a pest categorisation of Spodoptera litura (Lepidoptera: Noctuidae) for the EU. S. litura is widely distributed across South and East Asia and Oceania. It is established in tropical and subtropical regions where there are no, or few, frost days each year. It can extend its range into cooler temperate regions during summer months. S. litura is highly polyphagous feeding on hosts within at least 40 botanical families, including economically important crops within B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…To date, over 1600 species of insects have been identified as Lepidoptera, many of which are agricultural and forest pests [ 10 ]. Spodoptera litura and Helicoverpa armigera are two typical lepidopteran pests and do great harm to plenty of economic crops, such as tomatoes, cotton, and maize [ 11 , 12 ]. It was reported that Nosema spodopterae isolated from S. litura and H. armigera showed a high virulence [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, over 1600 species of insects have been identified as Lepidoptera, many of which are agricultural and forest pests [ 10 ]. Spodoptera litura and Helicoverpa armigera are two typical lepidopteran pests and do great harm to plenty of economic crops, such as tomatoes, cotton, and maize [ 11 , 12 ]. It was reported that Nosema spodopterae isolated from S. litura and H. armigera showed a high virulence [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spodoptera litura (Lepidoptera: Noctuidae) commonly known as tobacco cutworm or cotton (Cheng et al 2017) leafworm is a polyphagous pest, causes considerable damage to cotton (Gossypium hirsutum) and various other crops (Xue et al 2010;Bragard et al 2019). Failure to control S. litura and its resistance to various insecticides, lead to humongous economical loss (Ahmad and Gull 2017;Fand et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell and Tumlinson () note that S. eridania cannot survive extended periods of freezing temperatures. The EFSA PLH Panel () provides a map of the mean number of annual frost days in Europe, 1988‐2017. It shows that southern coastal areas of Portugal, Spain, France, Italy, Greece and Cyprus normally remain frost free year round.…”
Section: Pest Categorisationmentioning
confidence: 99%